In the Hands of Indigenous Peoples: The Future of Upland Coffee Regions in the Philippines - Chaves, Carmeli Marie C. (Review of Women's Studies, 2014)
This study presents the existing conditions of upland coffee farming regions in the Philippines. Using a multiple case study approach to examine selected coffee growing municipalities in the Cordillera and Mindanao, the paper dissects the issues affecting the coffee industry and their implications on the lives of the indigenous communities that nurture the coffee, especially the women and elderly. The author proffers that the future of the coffee industry depends on sustaining and empowering the indigenous coffee growers, which in turn can also help sustain the indigenous communities.